Empirical evidence for discrete neurocognitive subgroups in patients with non-psychotic major depressive disorder: clinical implications. Issue 16 (22nd April 2018) - Pu, Shenghong; Noda, Takamasa; Setoyama, Shiori; Nakagome, Kazuyuki
Abstract: Background: Neuropsychological deficits are present across various cognitive domains in major depressive disorder (MDD). However, a consistent and specific profile of neuropsychological abnormalities has not yet been established. Methods: We assessed cognition in 170 patients with non-psychotic MDD using the Brief Assessment of Cognition in Schizophrenia and the scores were compared with those of 42 patients with schizophrenia as a reference for severity of cognitive impairment. Hierarchical cluster analysis was conducted to determine whether there are discrete neurocognitive subgroups in MDD. We then compared the subgroups in terms of several clinical factors and social functioning. Results: Three distinct neurocognitive subgroups were found: (1) a mild impairment subgroup with near-normative performance and mild dysfunction in motor speed; (2) a selective impairment subgroup, which exhibited preserved working memory and executive function, but moderate to severe deficits in verbal memory, motor speed, verbal fluency, and attention/information processing speed; and (3) a global impairment subgroup with moderate to severe deficits across all neurocognitive domains, comparable with deficits in schizophrenia. The global impairment subgroup was characterized by lower pre-morbid intelligence quotient (IQ). Moreover, a significant difference between groups was observed in premorbid IQ ( p = 0.003), antidepressant dose ( p = 0.043), antipsychotic dose ( p = 0.013), or anxiolytic dose ( p < 0.001). Conclusions: These results suggest the presence of multiple neurocognitive subgroups in non-psychotic MDD with unique profiles, one of which exhibits deficits comparable to those of schizophrenia. The results of the present study may help guide future efforts to target these disabling symptoms using different treatments.